Zalivʺ Vel. Kn. Konstantina po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1917 g. / Sʺemka i chertilʺ Kapitan malago plavanīi︠a︡ P. Simonʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1917)
Relief shown by form lines and spot heights. Depth shown by soundings.; Title translation: Gulf of Grand Duke Konstantin, according to the survey of the Hydrographic Expedition of the Eastern Ocean in 1917.; Greenwich meridian. Coordinates given on map of Constantine Bay (also known as Konstantina Bay or Gulf of Grand Duke Konstantin): 54°04'32.0"N 137°24'34.0"E.; "Masshtabʺ 1/42000 ili 500 s. vʺ 1 di︠u︡ĭmi︠e︡" = Scale 1/42000 or 500 fathoms in 1 inch.; "371" -- hand written bottom right margin Grayscale; 1:42,000